Punjabi immigrant mobility in the United States : adaptation through race and class - Mitra, Diditi (Palgrave Macmillan, 2012)
How did so many Punjabi immigrants come to find themselves behind the wheels of so many New York City taxi cabs, and what do their stories have to teach us about how immigrants must navigate life in a new society? Diditi Mitra analyzes how race and class influence settlement patterns in the United States, based on her extensive interviews with 59 Punjabi taxi drivers, organizers of the New York Taxi Workers Alliance, laywers who represent drivers in taxi courts, owners of taxi fleets, and an official of the New York Taxi and Limousine Commission. What emerges is an unprecedented exploration into how society shapes the 'choices' made by immigrants as they adapt to America.